Studi Pelaksanaan Program Keselamatan dan Kesehatan Kerja pada Proyek Pembangunan RS Indriati Solobaru Bagian Mechanical Electrical oleh PT. Indomeco Primatama - Nurseto, Adhi, Dwi Astuti, SKM. M.Kes, Dr. Suwadji, M.Kes (2016)
The research aims to investigate the implementation of Occupational Health and Safety program in construction projects Indriati Solobaru Hospital in mechanical and electrical parts by PT Indo Meco Primatama. The type of the research is non-experimental research with a descriptive survey method and using purposive sampling technique. The research concluded that PT. Indo Meco Primatama as the service provider of mechanical and electrical parts in construction projects of Indriati Solobaru Hospital has placed the Occupational Health and Safety organization in its organizational structure, with the selection of human resources trained experts in Occupational Health and Safety which is accompanied by a plan concept of Occupational Health and Safety budget allocated to personal protective equipment, facilities and infrastructure in Occupational Health and Safety, Occupational Health and Safety promotion program, and Occupational Health and Safety qualified personnel. However, PT. Indo Meco Primatama has not made P2K3 yet and carried out medical examinations to prospective labor and health checks are conducted regularly to the work force. Safety Officer of PT. Indo Meco Primatama has run Occupational Health and Safety program, in the form of safety talk, safety patrols, cleanliness and order program project area, as well as inspection of working tools. However, Safety officer of PT. Indo Meco Primatama has not carry out hazard identification and risk assessment at the beginning of the project and in each development project.